Little Puffin's first flight - London, Jonathan, 1947- (Alaska Northwest Books, 2015)
Follows a family of puffins from the time the parents greet one another off the coast of Alaska and prepare to raise a family, through the care of their fragile egg and ravenous chick, to Little Puffin's first flight across and into the sea. Includes facts about puffins.